2020
DOI: 10.1371/journal.pone.0234050
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the microbiome of ectoparasitic louse flies feeding on migratory raptors

Abstract: Louse flies (Diptera: Hippoboscidae) are obligate ectoparasites that often cause behavioral, pathogenic, and evolutionary effects on their hosts. Interactions between ectoparasites and avian hosts, especially migrating taxa, may influence avian pathogen spread in tropical and temperate ecosystems and affect long-term survival, fitness and reproductive success. The purpose of this study was to characterize the vector-associated microbiome of ectoparasitic louse flies feeding on migrating raptors over the fall m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…In addition to participating in host immune metabolism, microbes that colonize the gut are also influenced by host genetics ( Lucas and Heeb, 2005 ; Whittaker et al, 2016 ; Song et al, 2020 ), feeding habits or diet ( Preest et al, 2003 ; Blanco, 2014 ), developmental stages ( González-Braojos et al, 2011 ; Escallón et al, 2019 ; Zhu et al, 2021 ), living conditions ( Wu et al, 2021 ), and specific behaviors such as migration ( Wienemann et al, 2011 ; Lewis et al, 2017 ; McCabe et al, 2020 ) and parasitism ( Ruiz-Rodriguez et al, 2018 ). During the long-term co-evolution of host and gut microbes, a unique and stable gut microbial community or gut microbiota is formed in the host.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to participating in host immune metabolism, microbes that colonize the gut are also influenced by host genetics ( Lucas and Heeb, 2005 ; Whittaker et al, 2016 ; Song et al, 2020 ), feeding habits or diet ( Preest et al, 2003 ; Blanco, 2014 ), developmental stages ( González-Braojos et al, 2011 ; Escallón et al, 2019 ; Zhu et al, 2021 ), living conditions ( Wu et al, 2021 ), and specific behaviors such as migration ( Wienemann et al, 2011 ; Lewis et al, 2017 ; McCabe et al, 2020 ) and parasitism ( Ruiz-Rodriguez et al, 2018 ). During the long-term co-evolution of host and gut microbes, a unique and stable gut microbial community or gut microbiota is formed in the host.…”
Section: Introductionmentioning
confidence: 99%
“…The high prevalence of louse flies found on raptors could be partially explained by the presence of one species commonly found on them: Icosta americana . This species was dominant on raptors in studies from the United States ( McCabe et al, 2020 ), Mexico ( Bolaños-García et al, 2018 ), and, despite the small sample size, the only louse fly species found on American Kestrels in Argentina ( Liébana et al, 2011 ), and on hawks and owls in Toronto, Canada ( Bennett, 1961 ). It was also dominant in this study, which is not surprising since this louse fly is common in the southern Nearctic Region, reaching as far north as Ontario and Quebec in Canada, and less abundant in the Neotropics ( Bequaert, 1955 ; Maa, 1969d ).…”
Section: Discussionmentioning
confidence: 99%
“…Most large and detailed studies date from the 1950s and 1960s, with the work of Bequaert (1952 , 1953 , 1954 , 1955 , 1956) and Maa (1963 , 1964 , 1965 , 1965 , 1969a , 1969b , 1969c , 1969d , 1969e ). There has been a recent surge of research investigating host specificity ( Lehikoinen et al, 2021 ), microbiomes ( McCabe et al, 2020 ) and their prevalence ( Meiβner et al, 2020 ; Sychra et al, 2020 ). However, these recent studies are often limited to one host in a specific region; e.g., Osprey ( Pandion haliaetus (Linnaeus)) from Baja California, Mexico ( Rodríguez-Estrella and Rivera-Rodríguez, 2019 ); Great Horned Owls ( Bubo virginianus (Gmelin)) from Baja California, Mexico ( Bolaños-García et al, 2018 ); Eleonora's falcon ( Falco eleonorae Gene) from Canary Islands ( Gangoso et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The external factors that influence the microbiome of these parasite are likely more limited than, for example, free-living animals because of their specialized diets and their limited movement in the environment due to their host dependence. The microbial composition of these taxa is however part of the holobiont (characterized by a multidimensional interaction between the bacteria and the host, and also the many other species living in or around it; see also Ben-Yosef et al ., 2017; McCabe et al ., 2020; Doña et al ., 2021) and as such several factors (e.g. parasite genetics, host ecology and evolution, abiotic environment, bacterial interactions and/or stochastic events) may act as potential drivers of a parasite's microbial community.…”
Section: Introductionmentioning
confidence: 99%